Low complexity signal detection algorithm based on Newton iterative algorithm - Gang LIU; Zengjin LOU; Qinhua LIN; Yi GUO (Tongxin xuebao)
In order to solve the problems of high computational complexity and slow convergence rate of ultra-massive MIMO detection in terahertz communication system, the low complexity signal detection algorithm based on Newton iterative algorithm was proposed.By improving the initial matrix and adding step factor in Newton iteration algorithm, the complexity of the algorithm was reduced, and the convergence speed was increased.By adding adjusting factors, the stability and reliability of the algorithm were guaranteed, and the applicability of the algorithm was also increased.Simulation results show that the proposed algorithm have lower computational complexity and faster convergence speed compared with traditional schemes.When the number of iterations is three, the detection performance is close to MMSE algorithm.